A poisson approximation in an urn model with indistinguishable balls - Menon V.V.; Indira N.K. (My University, 2025)
Let n indistinguishable balls be distributed in m urns such that all (m+n-1m-1) distributions are equally probable, and consider the number Mk of urns containing k balls each (k≥0). If m→∞ and n m→0 or ∞, the distribution of Mk can be approximated by a suitable Poisson distribution; we obtain estimates of the errors in such an approximation to the probability function and to the distribution function of Mk for large but finite m. A similar result is obtained for the model where no urn is allowed to be empty. The method used is elementary. © 1990.